Les sols (péri)urbains à l’épreuve du discours sur le primat du local - Élisabeth Rémy; Nolwenn Gauthier; Marine Canavese (Développement Durable et Territoires)
The enthusiasm for short food supply chains questions agri-food systems’ ecologisation. In that respect, the quality of plants growing on (peri) urban soils challenges the Risk Society and the controversial assessment of it. One can observe a struggle between cognitive and political frameworks in relation to this dialectic of knowledge production and ignorance on urban (peri) soils. Moreover, in the name of crops in urban soil development, cultivation off the ground is paradoxically chosen, which raises numerous technical, anthropological and political questions. Based on investigations carried out over several years, this article addresses the complex mechanisms that produce ignorance on an emerging object, that is, the nurturing urban soil valued in the name of local primacy.